Comparative study between activated carbon and biochar for phenol removal from aqueous solution - Elbidi, Moammar; Hewas, Agab; Asar, Rajab; Mohd Salleh, Mohamad Amran (North Carolina University, 2021)
Removal of phenol from wastewater using local biochar (BC) was investigated, while using activated carbon (AC) as a reference material. The main parameters affecting the sorption process were initial concentration, contact time, pH, and temperature. Statistical analysis of the results showed that the maximum removal percent when using AC and BC were 95% and 55%, respectively. Experimental data showed that the removal of phenol has fast kinetics and reached equilibrium within 5 minutes. The Langmuir and Freundlich isotherm models were applied to fit the adsorption experimental data. Pseudo-first order and pseudo-second order kinetic models were employed.